Effects of COVID-19 Misinformation on Information Seeking, Avoidance, and Processing: A Multicountry Comparative Study. Issue 5 (October 2020) - Kim, Hye Kyung; Ahn, Jisoo; Atkinson, Lucy; Kahlor, Lee Ann
We examined the implications of exposure to misinformation about COVID-19 in the United States, South Korea, and Singapore in the early stages of the global pandemic. The online survey results showed that misinformation exposure reduced information insufficiency, which subsequently led to greater information avoidance and heuristic processing, as well as less systematic processing of COVID-19 information. Indirect effects differ by country and were stronger in the U.S. sample than in the Singapore sample. This study highlights negative consequences of misinformation during a global pandemic and addresses possible cultural and situational differences in how people interpret and respond to misinformation.